2016
DOI: 10.1017/s1368980016001531
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adherence to Dietary Approaches to Stop Hypertension (DASH) diet indices and incidence of depression during up to 8 years of follow-up

Abstract: Objective: Our aim was to evaluate the relationship between adherence to different Dietary Approaches to Stop Hypertension (DASH) diet indices and the risk of depression. Design: In a prospective study we assessed 14 051 participants of a dynamic (permanently ongoing recruitment) prospective cohort (the Seguimiento Universidad de Navarra (SUN) Project), initially free of depression. At baseline, a validated FFQ was used to assess adherence to four previously proposed DASH indices (Dixon, Mellen, Fung and Günth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…Others have operationalized DASH diet accordance differently, and some clinical outcomes have been found to be differentially associated with these various indices. 40,41 Third, data on some important factors related to dietary intake and potentially to CKD, such as food additives 42 , nutritional supplements 43 , availability of healthful foods in neighborhood stores and physical activity 44 were unavailable. Fourth, some level of error has been associated with the measurement of food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Others have operationalized DASH diet accordance differently, and some clinical outcomes have been found to be differentially associated with these various indices. 40,41 Third, data on some important factors related to dietary intake and potentially to CKD, such as food additives 42 , nutritional supplements 43 , availability of healthful foods in neighborhood stores and physical activity 44 were unavailable. Fourth, some level of error has been associated with the measurement of food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of recommended dietary patterns such as the DASH, Mediterranean, or USDA MyPlate Diets might help manage these disorders, as well improve overall health. lower risk of developing depression over the 8.5 years of a follow-up study by PerezCornago et al (128). In addition, a balanced Japanese dietary pattern (high intakes of vegetables, fruits, mushrooms, and soy products) and adequate serum folate intake were associated with less depression (129).…”
Section: Mediterranean Dietmentioning
confidence: 92%
“…However, this dietary pattern is not as well researched and only a single cohort study was available (Perez‐Cornago et al . ), which compared four variants of the DASH diet. Only one DASH diet score, proposed by Fung et al .…”
Section: The Study Behind the Headlinesmentioning
confidence: 99%
“…No significant risk reduction for depressive outcomes was found for any estimates calculated for the DASH diet. However, this dietary pattern is not as well researched and only a single cohort study was available (Perez-Cornago et al 2017), which compared four variants of the DASH diet. Only one DASH diet score, proposed by Fung et al (2008), was found to be related to reduced risk of depression (HR = 0.63; 95% CI: 0.41, 0.95).…”
Section: The Study Behind the Headlinesmentioning
confidence: 99%